Microbial activity and biodiversity responding to contamination of metal(loid) in heterogeneous nonferrous mining and smelting areas. (July 2019) - Liu, Jian-li; Yao, Jun; Lu, Chao; Li, Hao; Li, Zi-fu; Duran, Robert; Sunahara, Geoffrey; Mihucz, Victor G.
Abstract: The combined contamination of nonferrous metal(loid) mining and smelting areas is a global issue, in need of urgent management. To our knowledge, this is the first report of microbial activities by microcalorimetry in specific nonferrous metal(loid) tailings with oligonutrition and high contents of toxic metal(loid)s. Dynamics of bacterial diversity were also characterized. Here we show that tailings had low microbial activities ( P max = 64.1–331 μW g −1 ), which were accelerated by the presence of dipotassium phosphate ( P max = 346–856 μW g −1 ), as measured by microcalorimetry. Frequent detection of S- and metal-resistant related genera and differences of Thiobacillus and Acidithiobacillus abundances indicated that the tailings were in an early stage of acidification. It has been further confirmed by the presence of a weak acid environment and secondary sulfur associated minerals, such as Sb2 S3, FeAsS, FeS2, and CuFeS2 . During the acidification process, phosphate, metal(loid)s, and microbial activity were correlated to the bacterial communities. It is suggested that the bacterial communities have metabolic capacities with a high potential for the use in management processes of multi-contaminated nonferrous metalliferous tailings. Highlights: Effects of tailing's nonferrous metal(loid)s on microbe. Microbial activity and diversity were determined by microcalorimetry and sequencing. The tailings had low basal microbial metabolism capacity. Abundances of Thiobacillus and Acidithiobacillus suggested the tailings acidification. Phosphate, metal(loid)s and microbial activity correlated to the bacterial community.